2003
DOI: 10.1046/j.1365-2591.2003.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral trioxide aggregate (MTA) and calcium hydroxide as pulp-capping agents in human teeth: a preliminary report

Abstract: Although the results favour the use of MTA, more studies with larger samples and a longer follow up are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
306
1
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(357 citation statements)
references
References 30 publications
27
306
1
12
Order By: Relevance
“…MTA also contains bismuth oxide, which increases its radiopacity, and is absent in the PC 3,6,17 . Several studies 2,4,5,7,10,11,12,14,16,17 have reported excellent results when using MTA over pulp. However, only two studies reported the use of Portland cement in conservative pulp therapy with considerable success in rats 17 and dogs 7 , complying with the present results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MTA also contains bismuth oxide, which increases its radiopacity, and is absent in the PC 3,6,17 . Several studies 2,4,5,7,10,11,12,14,16,17 have reported excellent results when using MTA over pulp. However, only two studies reported the use of Portland cement in conservative pulp therapy with considerable success in rats 17 and dogs 7 , complying with the present results.…”
Section: Discussionmentioning
confidence: 98%
“…MTA has been used in pulp capping procedures in animal 5,10,12 and human teeth, 2 and demonstrated remarkable success compared to calcium hydroxide. Previous studies claim similar success rates also after pulpotomies 7,14 .…”
Section: Introductionmentioning
confidence: 99%
“…One of them (Aeinehchi et al 2003), a preliminary study, compared MTA to Dycal ® in human permanent teeth over three time intervals. In the study, however, a sizable number of patients (6) discontinued the treatment prior to extraction of the teeth with the result that some time intervals had only two teeth available for histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to test the pulp healing ability of MTA on human teeth before its routine clinical application (ISO 1997). Except for few studies on the clinical and radiographic outcomes of direct pulp capping with MTA on human primary (Farsi et al 2005, Maroto et al 2005, Maroto et al 2006 and permanent (Farsi et al 2006) teeth, there seem to be only four publications in the literature (Aeinehchi et al 2003, Caicedo et al 2006, Chacko & Kurikose 2006, Iwamoto et al 2006, in which the response of human pulp to MTA has been histologically studied. The results of the latter studies on humans corroborated those reported in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Since MTA was introduced by Torabinejad at Loma Linda University, California, USA, it has been widely studied as a material of choice for root-end filling [9][10][11][12] , direct pulp capping [13][14][15] , perforation repair in roots or furcations 16,17) , and apexification 18,19) . In addition, it is useful for the troublesome strip perforations and perforating resorptive defects 20) .…”
Section: Introductionmentioning
confidence: 99%